The AMA handbook of financial risk management - Hampton, John J. , 1942- (American Management Association, 2011)
Managing financial risks comes down to understanding how to reduce a complex business environment into workable concepts and models. This guide provides readers with the tools they need for dealing with the most important areas of financial decision making. It clarifies the factors that affect the value of a firm